A proposed workbook in algebra for an agricultural school - Flores, Anita V. (Animo Repository, 1989)
The purpose of the study is to develop and evaluate a workbook in algebra for senior agriculture high school students. This workbook is intended as an enrichment material in the teaching of the subject. Specifically, it sought answers to the following questions. 1. Are the items in the problem set congruent with the objectives of the lesson for each chapter? 2. Is the readability level of the workbook appropriate for the target group? Since individualizing instruction will enable the students to profit more from the learning process. The results of this study should give interesting insights into the development/construction of more instructional materials in the different subject areas. The readability of the workbook was measured using Flesch Readability Formula, while questionnaire were administered to 5 competent instructors/professors who have taught in an agricultural school for at least three years to find out suggestions and corrections as to whether the items in the problem set are parallel with the objectives of the lessons. As a result of the review, the reviewers concluded that the items in the problem set are congruent with the objectives of the lessons as revealed by the total average of their responses which is 9.6. They also concluded that the workbook is appropriate for the target group, and agreed that the scope type fits the purpose of the study. The result of the test on the readability of the workbook, the computed reading ease score is 65.514. This is within the standard range which indicates that the material is readable by the target group, while the computed human interest score is 29.476 which falls under the bracket interesting. Within the limits of the study, the results imply that this developed learning material for senior agriculture high school students could be an effective tool for a mathematics teacher. This workbook is also as effective as the traditional lecture method of instruction because of the inclusion of mathematical concepts that are needed in answering the problem set. This implies further that this workbook could be proposed for use in the teaching of the subject. Pertinent to the findings and conclusions of the study, the following conclusions are offered: 1. Since individualizing instruction is an effective instructional technique, teachers should attend in-service trainings, conferences or seminars on workbook making in their subject areas. This developed workbook is recommended for use as supplement in classroom instruction particularly for agricultural high schools. 3. It is also recommended as supplement for remedial teaching for those students who have not mastered the lessons taught in the regular classroom hours and for those who often absent themselves due to poverty or illness. 4. Other studies should be made along instructional materials to include other units of mathematics like trigonometry and other subject areas.